2023
DOI: 10.1177/00031348231162706
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable Factors Attributing to Superior Mesenteric Vein Thrombosis and Acute Mesenteric Ischemia

Abstract: Acute mesenteric ischemia is rare and can be difficult to diagnose due to vague symptoms often endorsed by patients. It can be fatal if not discovered in time, as it can lead to bowel ischemia, sepsis, and ultimately death. Here, we present a case of a 23-year-old female with hepatic steatosis, obesity, and 5-year history of birth control use who developed acute mesenteric ischemia secondary to superior mesenteric venous (SMV) thrombosis, requiring small bowel resection of 238 cm out of 480 cm (49.5%) after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Immediate local contrast imaging revealed some thrombus formation in the mesenteric veins ( Figure 1F ). In this study, several factors were identified to be increasing the likelihood of acute mesenteric venous thrombosis (MVT), including smoking, high blood pressure, peritonitis, hemoglobin levels, albumin levels, intraperitoneal free fluid, decreased intestinal wall enhancement, and bowel distension ( 28 ). Additionally, factors such as a history of blood clotting problems, splenectomy, and symptoms like nausea, vomiting, abdominal pain, tenderness, and distension, along with lab results showing high plasma lactate levels and white blood cell counts, must be considered ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immediate local contrast imaging revealed some thrombus formation in the mesenteric veins ( Figure 1F ). In this study, several factors were identified to be increasing the likelihood of acute mesenteric venous thrombosis (MVT), including smoking, high blood pressure, peritonitis, hemoglobin levels, albumin levels, intraperitoneal free fluid, decreased intestinal wall enhancement, and bowel distension ( 28 ). Additionally, factors such as a history of blood clotting problems, splenectomy, and symptoms like nausea, vomiting, abdominal pain, tenderness, and distension, along with lab results showing high plasma lactate levels and white blood cell counts, must be considered ( 29 ).…”
Section: Discussionmentioning
confidence: 99%